2020
DOI: 10.3390/jof6030130
|View full text |Cite
|
Sign up to set email alerts
|

Rearing and Maintenance of Galleria mellonella and Its Application to Study Fungal Virulence

Abstract: Galleria mellonella larvae have been widely used as alternative non-mammalian models for the study of fungal virulence and pathogenesis. The larvae can be acquired in small volumes from worm farms, pet stores, or other independent suppliers commonly found in the United States and parts of Europe. However, in countries with no or limited commercial availability, the process of shipping these larvae can cause them stress, resulting in decreased or altered immunity. Furthermore, the conditions used to rear these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 49 publications
(88 reference statements)
1
36
0
Order By: Relevance
“…The advantage of using G. mellonella as a model for the study of pathogenicity in fungi is the ease of use, that is, the inoculation of the pathogen involves only a hind leg and a syringe, and they can be maintained at variable temperatures ranging from 25 to 37 °C. The innate immune response is an important component in the immune response to pathogenic infections and the reports show strong correlation between fungal pathogenicity results in larvae and mice [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of using G. mellonella as a model for the study of pathogenicity in fungi is the ease of use, that is, the inoculation of the pathogen involves only a hind leg and a syringe, and they can be maintained at variable temperatures ranging from 25 to 37 °C. The innate immune response is an important component in the immune response to pathogenic infections and the reports show strong correlation between fungal pathogenicity results in larvae and mice [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This non-mammalian model can be maintained easily and inexpensively in laboratory conditions, at different temperatures, including the human temperature 37 • C. Similarly to mammalian models, this insect develops a specific immune response against different microbial infections (Pereira et al, 2018). Therefore, this insect has been used to study the fungal virulence and pathogenesis (Benaducci et al, 2016;Firacative et al, 2020;Grizante Barião et al, 2020) and to evaluate the efficacy of the antifungal agents against different fungal species (Singulani et al, 2019;de Castro Spadari et al, 2020). The results reported in the present study showed that early treatment with EAF from P. pluviosa combined with AmB was effective in controlling C. neoformans infection with no toxicity to larvae, supporting the in vitro results.…”
Section: Discussionmentioning
confidence: 99%
“…and more recently Firacative et al . proposed an optimal method to rear G. mellonella in laboratories for microbiological studies (dietary components, description of environmental conditions, and a detailed protocol for all life stages of G. mellonella ) [ 32 , 38 ].
Figure 2.
…”
Section: Galleria Mellonella Modelmentioning
confidence: 99%
“…Galleria mellonella has been used for the complex study of host–microbe interactions, especially host-fungi interactions [ 4 , 6 , 24–30 ]. This model is now recognized as a pertinent model to the study of the fungal infections [ 31 , 32 ]. Aspergillus fumigatus remains one of the most common pathogenic fungi known to colonize the respiratory tract of patients with chronic lung diseases (e.g.…”
Section: Introductionmentioning
confidence: 99%